The evolution of Ondo kingdom over 500 years (1510-2010) - Ajayi, Simeon Ibidayo (Ibadan, Nigeria; Spectrum Books Limited, 2013)
The Evolution of Ondo Kingdom: Over 500 years ( 1510-2010 +) is an account of different aspects of the growth and development of the Ondo Kingdom over the past 500 years, commencing with first monarch, a female, called Pupupu, to the current Monarch, Oba Dr. Victor Adesimbo Kiladejo Jilo III with 41 other monarchs in between. The topics in the book's 10 chapters covering various aspects in the evolution of Ondo Kingdom include: the influence of Christianity, culture and tradition, evolution of government , politics , the economy, education and administration and of course the challenges of growth progress and prosperity . They were expertly written. All the authors are agreed that the Osemawe dynasty has survived as a highly revered tradition that has remained vibrant till today.
Includes index.
oej 19/11/2019
Loans
Keywords: Kings and rulers; Ondo Kingdom; Nigeria--Ondo State